Resilience in Teaching: Uncovering Grit Differences Based on Marital Status in Madrasah English Teachers - Afiah, Nur; Fakhruddin, Zulfah; Samaun, Siti Salina (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This research aims to analyze grit differentiation based on marital status among English teachers in madrasahs. A mixed-method approach was used, combining quantitative and qualitative data collection. The study identified three forms of grit differences among English language teachers: teaching spirit, persistence in work, and consistency of interest in the teaching profession. These differences appear to be influenced by marital status. Married teachers tend to have higher grit levels compared to their unmarried counterparts. This difference can be attributed to the role of a supportive partner, who provides a vital support system within the family, enhancing mental resilience through emotional, social, and economic support. Married teachers are also more likely to have a long-term commitment to their profession, contrasting with unmarried teachers, who may often exhibit less stability in their motivation.